BUSUU APPLICATION IN TEACHING SPEAKING ABILITY AT ISLAMIC SCHOOL - Mohamad Adam Firdaus (Sindoro: Cendikia Pendidikan, 2023)
This study used a quasi- experimental method with two classes, namely class X A as the experimental class and class X B as the control class. After collecting the data, the researcher analysed the data using the t-test. Based on the results, the researchers found the average pre-test in the experimental class is 35,5 and the average post-test value in the experimental class is 54,3. Meanwhile, the average pre-test in the control class is 35,75 and the average post-test value in the control class is 43,15. According the result of the data, the value of tobservation (4,72) > ttable (2,02) in 5%, and tobservation (4,72) > ttable (2,71) in 1%. So, Ho is rejected and Ha is accepted. which means Busuu Application is effective in teaching speaking ability.